Hepatoprotective activities of a sesquiterpene-rich fraction from the aerial part of Cichorium glandulosum - Yang Wei-Jun; Luo Yu-Qin; Aisa Haji; Xin Xue-Lei; Totahon Z; Mao Yan; Hu Meng-Ying; Xu Lei; Zhang Rui-Ping (BMC, 2012)
Abstract Background Cichorium glandulosum Boiss. et Huet is used for treatment of liver disorders, and its effects are attributed to sesquiterpenes. This study aims to investigate the hepatoprotective effects of a sesquiterpene-rich fraction (SRF) from the aerial part of C. glandulosum on carbon tetrachloride (CCl4)-induced acute hepatotoxicity in mice, and on priming with Bacillus Calmette-Guerin (BCG) followed by lipopolysaccharide (LPS)-induced immunological liver injury in mice. Methods SRF was suspended in water and administered to mice at 0.05, 0.10 and 0.20 g/kg body weight for 7 consecutive days. An active control drug (bifendate pills) was suspended in distilled water and administered to mice at 0.40 g/kg body weight for 7 consecutive days. Hepatotoxicity was induced by intraperitoneal injection of 0.1% CCl4 (0.2 mL/mouse) at 13 h before the last drug administration, or by tail intravenous injection of BCG (0.2 mL/mouse) before the first drug administration and LPS (0.2 mL/mouse; 8 μg) at 15 h before the last drug administration. Blood samples and the livers were collected for evaluation of the biochemical parameters of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and total bilirubin (TBIL). Results SRF significantly reduced the impact of CCl4 toxicity. The highest dose of SRF (0.20 g/kg) was the most effective, reflected by significant reductions in the levels of AST (P = 0.001), ALT (P = 0.000) and TBIL (P = 0.009). The serum enzymatic levels induced by BCG and subsequent LPS injection were significantly and dose-dependently restored by SRF, reflected by significant reductions in the levels of AST (P = 0.003), ALT (P = 0.003) and TBIL (P = 0.007) for the highest dose of SRF (0.20 g/kg). Conclusion SRF is hepatoprotective in animal models of chemical and immunological acute liver injury.